Caracterización fisicoquímica de un lactosuero: potencialidad de recuperación de fósforo - Callejas Hernández, Judith; Prieto García, Francisco; Reyes Cruz, Víctor E.; Marmolejo Santillán, Yolanda; Méndez Marzo, María A. (Acta Universitaria, 2012)
The objective of this work was to characterize in the dairy industry of Santiago de Anaya in Hidalgo the whey obtained and to assess the recovery of phosphorus. For this composite sampling was performed: was determined, according to Mexican standards, electrical conductivity, pH, redox potential, zeta potential, particle size and distribution, chemical oxygen demand, total solids, volatile and suspended, fats, turbidity, protein, lactose, lactic acid and phosphorus. We used a process of electrocoagulation with Al and Ru2O3 electrodes for removing organic load. The average results showed that a whey acidic (pH = 4,8), pZ of -4,02 mV, which has high organic loads (COD> 100 000 mg O2/L), among which contained lactose (4,4 g/dL), lactic acid (0,27 g/dL), fat (0,83 g/dL), protein (1,08 g/dL) and PO43- of 20,8 g/dL. Following 24 hours of electrocoagulation, was achieved 84 % removal of COD and recover 17,4 g/dL PO43-aqueous phase clean and 0,07 g/kg of flocculated solid representing a total of 87 %.
Keywords: Array; Array; Array; Array; Array